2022
DOI: 10.1038/s41598-022-22638-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on quantification of aortic stiffness by ultrasound time-harmonic elastography

Abstract: Smoking is a significant cardiovascular risk factor that causes stiffening of the central arteries, especially the aorta. While vessel stiffness can be determined indirectly by measuring pulse wave velocity, elastography allows image-based determination of vessel stiffness while at the same time providing information on vascular morphology. This study compares abdominal aortic wall stiffness as measured by ultrasound time-harmonic elastography (THE) in fifteen smokers and fifteen age-matched non-smoking contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Smoke is one of the most important risk factors for cardiovascular disease. Studies showed that smoking is a strong risk factor for increased arterial stiffness [ 68 ] and directly associated with the number of daily cigarettes smoked [ 69 ]. The detrimental effect of smoking is greater when combined with the other risk factors, such as dyslipidemia, inflammation, and arterial calcification.…”
Section: Behavior Risk Factorsmentioning
confidence: 99%
“…Smoke is one of the most important risk factors for cardiovascular disease. Studies showed that smoking is a strong risk factor for increased arterial stiffness [ 68 ] and directly associated with the number of daily cigarettes smoked [ 69 ]. The detrimental effect of smoking is greater when combined with the other risk factors, such as dyslipidemia, inflammation, and arterial calcification.…”
Section: Behavior Risk Factorsmentioning
confidence: 99%